Promotion and Enhancement of Knowledge in Nursing - Jhon Henry Osorio-Castaño (Universidad de Antioquia, 2018)
Abstract: Knowledge is the product of the action of learning and has as requisite that it can be expressed and communicated to others.(1) According to Fawcett,(2) one of the central issues for the survival of nursing as a discipline is understanding the nature and structure of nursing knowledge. This can be interpreted as the clarity about that which should be investigated, what should be done in the practice, and what should be taught during the formation of professionals. Although research, practice, and formation have been based on the body of knowledge from other disciplines,(3) it is not possible to achieve autonomy and independence in practice, as a given right,(4) if progress is not made in the construction, consolidation, and appropriation of nursing's own knowledge. Hence, to promote the development of nursing knowledge requires three central elements: formation, practice, and research; and each of them transversed by other support elements, like the development and analysis of concepts, the use of medium-range theories, the use of a standardized language, and evidence-based nursing.